2020
DOI: 10.1098/rspb.2020.2085
|View full text |Cite
|
Sign up to set email alerts
|

Morphological divergence in giant fossil dormice

Abstract: Insular gigantism—evolutionary increases in body size from small-bodied mainland ancestors—is a conceptually significant, but poorly studied, evolutionary phenomenon. Gigantism is widespread on Mediterranean islands, particularly among fossil and extant dormice. These include an extant giant population of Eliomys quercinus on Formentera, the giant Balearic genus † Hypnomys and the exceptionally large † Leithia melitensis of Pleistocene Sic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Based on known morphological differences in M. pennsylvanicus , especially for Atlantic region islands (Miller 1896, Chamberlain 1954, Wheeler 1956), we anticipated and detected an association between shape and size (i.e. static allometry), a common pattern across rodents (Marcy et al 2016, Hennekam et al 2020). Furthermore, there is a narrower range of PC scores among populations in the ventral shape data compared to dorsal shape.…”
Section: Discussionmentioning
confidence: 74%
“…Based on known morphological differences in M. pennsylvanicus , especially for Atlantic region islands (Miller 1896, Chamberlain 1954, Wheeler 1956), we anticipated and detected an association between shape and size (i.e. static allometry), a common pattern across rodents (Marcy et al 2016, Hennekam et al 2020). Furthermore, there is a narrower range of PC scores among populations in the ventral shape data compared to dorsal shape.…”
Section: Discussionmentioning
confidence: 74%
“…The maximum within-genus size difference is therefore expected to be larger than displayed in Figure 4. This absence within the dataset is exceptionally notable for the genus Eliomys , for which insular specimens were excluded from this study, but the largest population of which is found on the island of Formentera (Storch, 1978; Hennekam et al, 2020b). The results indicate that relatively large dormouse genera ( Eliomys and Glis ) are more variable in size than smaller genera ( Muscardinus and Glirulus ).…”
Section: Resultsmentioning
confidence: 94%
“…Considering the large size range within Gliridae, a common allometric trend within the family is to be expected. Strong correlations between size and shape have been identified within dormice species (Hennekam et al, 2020b), resulting in species- or genus-specific allometric trajectories. The size distribution within certain genera (e.g.…”
Section: Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple populations were included for widely dispersed species. Insular populations were avoided, as morphological variation in dormice linked with insularity is described in a previous study (Hennekam, Benson, et al, 2020). Even though sexual dimorphism is not considered to be present within dormice (Holden‐Musser et al, 2016), whenever possible, an equal representation of both sexes was included within the dataset.…”
Section: Methodsmentioning
confidence: 99%